Modifikasi Mambe Tampun dalam Pembentukan Karakter dan Kesadaran Hidup Sehat Siswa SMPN 7 Palangka Raya - Harvianto, Yudo; Ulfa, Zuly Daima; Perdana, Jeff Agung; Siskaevia, Siskaevia; Purnama Sari, Uswatun Hasanah; Razzi, Fahrul; Wahyudi, Arief Nur; Siahan, Frans Leo; Prescia, Winda (Universitas Hamzanwadi, 2025)
The purpose of the study was to analyze the effect of mambe tampun modification on character building and students' healthy living awareness. This research is a type of experimental research with the form of pre-experimental designs, namely one group pretest-posttest design. The population was 210 students of SMP Negeri 7 Palangka Raya. The sample was students of SMP Negeri 7 Palangka Raya selected by purposive sampling method as many as 57 students. The data analysis technique uses a prerequisite test analysis of parametric statistical tests, namely the T test of two paired samples. The instruments used were character building questionnaires and students' healthy living awareness. The results of the pretest value P-Value analysis show that the data is normally distributed because it has met the P-Value > α criteria, namely (0.080 > 0.05). The results of the post-test value P-Value show that the data is normally distributed because it has met the criteria of P-Value > α, namely (0.077 > 0.05). The P-Value > α criterion is (0.933 > 0.05), the P-Value > α criterion is (0.069 > 0.05). The conclusion of this study is that there is an effect of modification of the Mambe Tampun game on character building and healthy living awareness of SMPN 7 Palangka Raya students.